Does Climate Policy Affect The Price And Volume Of Indonesian Coal Exports? - Sekar Tri Widati; Nissa Nur Awaliyah; Ruth Abigail Tarigan (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
This study aims to investigate the impact of climate policies, such as the ParisAgreement and its derivatives, the Gasglow climate pact, on the reference coal priceand its effect on the volume of Indonesian coal exports. A qualitative approach,utilizing secondary data from various international level journals, data from theMinistry of Energy and Mineral Resources, the World Bank, and other relevantsources, was employed. The research method utilized literature study. The results ofthis study indicate Climate policies the Paris Agreement, the Glasgow Climate Pact,and benchmark coal price on Indonesia's coal export volume is limited do not have anotable effect the volume of coal exports do not significantly impact the reference.Recommendation for Policy makers should conduct a comprehensive assessment ofcoal export policies, with a particular focus on their alignment with the commitmentsoutlined in the Paris Agreement and the Glasgow Climate Pact. This assessmentshould include an examination of emissions targets and whether or not coal exportsare at odds with them.